2017
DOI: 10.21083/partnership.v12i1.3906
|View full text |Cite
|
Sign up to set email alerts
|

Research Impact Metrics: A Faculty Perspective

Abstract: With an increasing focus on scholarly communications in academic libraries, librarians are struggling with how best to support faculty with the location, interpretation, and appropriate use of metrics. Very little has been written about the faculty researcher perspective on metrics and, as a result, librarians may have a deep knowledge of the tools but have a more limited understanding of the users' viewpoint. Seventy-nine senior research faculty who were five or more years post-tenure were interviewed. Facult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Faculty knowledge and perception of OA publishing was the sole focus for Peekhaus and Proferes (2015), Rodriguez (2014), Mischo and Schlembach (2011), Lwoga and Questier (2014), and Gaines (2015). Research metrics has been another popular topic of focus for studies of faculty awareness and understanding; see for example Vinyard and Colvin (2018), Thuna and King (2017), DeSanto and Nichols (2017), and Sutton, Miles, and Konkiel (2018). Meanwhile, Diekema, Wesolek, and Walters (2014), Van Tuyl and Michalek (2015), and Weller and Monroe-Gulick (2015) focused only on faculty knowledge and skills pertaining to research data management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Faculty knowledge and perception of OA publishing was the sole focus for Peekhaus and Proferes (2015), Rodriguez (2014), Mischo and Schlembach (2011), Lwoga and Questier (2014), and Gaines (2015). Research metrics has been another popular topic of focus for studies of faculty awareness and understanding; see for example Vinyard and Colvin (2018), Thuna and King (2017), DeSanto and Nichols (2017), and Sutton, Miles, and Konkiel (2018). Meanwhile, Diekema, Wesolek, and Walters (2014), Van Tuyl and Michalek (2015), and Weller and Monroe-Gulick (2015) focused only on faculty knowledge and skills pertaining to research data management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, many past studies focused on specific researcher demographics; for example, the University of California's Report on Faculty Attitudes (2007) and Harley et al (2010) focused on elite R1 institutions; Peekhaus and Proferes (2015) focused only on faculty in Library and Information Sciences; and Thuna and King (2017) surveyed only "senior" researchers, 5+ years post-tenure. Vinyard and Colvin (2018) did evaluate faculty at a Doctoral/Professional institution, more comparable to SHSU, but focused only on one school within the university, in which faculty worked almost exclusively with undergraduate students; additionally, with only 66 responses, the sample size was small.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite these findings, researchers' confidence in citation indicators remains strong (Blankstein & Wolff-Eisenberg, 2019;Buela-Casal & Zych, 2012;Thuna & King, 2017). However, movements for disrupting the academic incentive system are on the rise, such as the Leiden Manifesto and the Declaration on Research Assessment (DORA) (Hicks et al, 2015; The American Society for Cell Biology, 2012).…”
Section: Researcher Perceptions Of Research Assessmentmentioning
confidence: 99%
“…With the increasing focus on short-term quantitative indicators for research assessment and resource allocation, institutions across the world have shifted priorities and sought expert advice on bibliometric indicators and databases, especially from academic libraries (Thuna & King, 2017). A survey study found that faculty members are more likely to consult with librarians on the use of the JIF, h-index, and citation counts for purposes related to promotion, tenure, and grants than for other purposes, highlighting the importance of these three indicators for evaluation purposes (Miles et al, 2018).…”
Section: Researcher Perceptions Of Research Assessmentmentioning
confidence: 99%
“…Despite the widespread availability of the h -index, no previous large-scale survey of academics seems to have elicited researchers’ attitudes towards it. For example, interviews with 79 senior faculty at a Canadian university about scholarly metrics did not produce any h -index attitudes (Thuna & King, 2017 ). Another study asked medical and physics postdocs at an Australian university whether they used the h -index (most did) but did not ask them what they thought of it (Derrick & Gillespie, 2013 ).…”
Section: Introductionmentioning
confidence: 99%